1996
DOI: 10.1111/j.1751-1097.1996.tb01859.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Cyclobutane Pyrimidine Dimer Photolyase in Cultured Fish Cells by UVA and Blue Light

Abstract: The cyclobutane pyrimidine dimer (CPD) photolyase in fish cells is known to be regulated by environmental factors, such as light, hydrogen peroxide and growth inhibition. The induction of CPD photolyase by light in cultured goldfish cells was dependent on the wavelength of the light, and UVA and blue light had high inductive activity. The spectrum for CPD photolyase activity was different from that for the induction. Treatment with blue or yellow light for a short time, which did not induce any CPD photolyase,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…if the photochemical law of reciprocity would hold, the mean UVBR, UVAR and PAR doses in the wind mixed surface layer (WML) would be sufficient to predict effects on plankton organisms. However, there are indications that this is not always the case, especially for repair processes (Zagarese et al 1998); not only the rate of photorepair, but also the induction of the repair system is light dependent (Mitani et al 1996). This means that under fluctuating irradiance conditions, as experienced by plankton in the WML, repair rates may not always be optimal.…”
mentioning
confidence: 83%
“…if the photochemical law of reciprocity would hold, the mean UVBR, UVAR and PAR doses in the wind mixed surface layer (WML) would be sufficient to predict effects on plankton organisms. However, there are indications that this is not always the case, especially for repair processes (Zagarese et al 1998); not only the rate of photorepair, but also the induction of the repair system is light dependent (Mitani et al 1996). This means that under fluctuating irradiance conditions, as experienced by plankton in the WML, repair rates may not always be optimal.…”
mentioning
confidence: 83%
“…However, we have reported before that blue light stimulates phrA expression . In the fungus Trichoderma harzianum (Berrocal-Tito et al, 1999) and in the goldfish Carassius auratus (Mitani et al, 1996;Mitani & Shima, 1995;Yasuhira et al, 1991) blue light as well as H 2 O 2 induces the transcription of the photolyase gene. Kihara et al (2004) showed that near-UV light (300-400 nm) and sunlight enhance the expression of the photolyase in the fungus Bipolaris oryzae.…”
Section: Upregulation Of Phra Expression Depends On Light Intensity Amentioning
confidence: 99%
“…Illumination was provided by two 30 W Vita-Lite ® (Duro-Test Canada) fluorescent tubes placed 1.5 m from the eggs. The spectral output of these lamps includes some longwave ultraviolet-A (320 to 400 nm = UV-A); photorepair mechanisms should have been active under this light regime (Mitchell et al 1993, Mitani et al 1996. The PAR (400 to 700 nm) output of these lamps, at the position where the eggs were incubated, was 0.03 W m -2 .…”
mentioning
confidence: 99%